Electrochemical impedance spectroscopy on porous electrodes - Gassa, Liliana Mabel (1990)
Electrochemical d.c. and a.c. measurements have been carried out on porous Raney nickel in H2-saturated 0.1 M, 1 M, and 6 M NaOH solutions atT=303 K and 333 K using rotating-disc and static-plaar electrodes. For comparison, measurements were also performed on graphite-cloth and graphite-felt electrodes. From polarization curves and current transients obtained in the potential range of the hydrogen evolution and hydrogen oxidation reactions the dependence of the electrocatalytic activity of Raney nickel on the prepolarization conditions was studied. Impedance spectra in the frequency range 1 mHzf 10 kHz were used to determine the characteristic pore parameters and to identify the kinetic behaviour of the porous electrodes by application of transfer function analysis using non-linear fit routines.